Severe Periodontal Disease Associated with Long-Term Treatment with Intravenous Immunoglobulin - Jôice Dias Corrêa; Amanda Leal Rocha; Lidiane Cristina Machado Costa; Denise Travassos; Wagner Henriques Castro; Gustavo Pompermaier Garlet; Rodrigo Santiago Gomez; Antônio Lúcio Teixeira; Tarcília Aparecida Silva (Case Reports in Dentistry)
Intravenous immunoglobulin (IVIG) is used in the treatment of neuropathy. This case report presents, for the first time, a patient with severe periodontal destruction after chronic therapy with IVIG. The patient reported having extracted his maxillary anterior teeth himself due to high mobility. Clinical examination and radiographic images show a generalized and severe periodontitis. No significant alterations in genetic or microbiological features were observed. The present case suggests that periodontal disease aggravation could be considered a new adverse effect of IVIG therapy. Postulated mechanisms are immune complexes formation, complement activation, and a direct effect in osteoclasts. In conclusion, it is important that patients that will receive IVIG treatment underwent dental evaluation.